2002
DOI: 10.1080/15572536.2003.11833150
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and constraint in growth and protein mineralization of ectomycorrhizal fungi under simulated nitrogen deposition

Abstract: Ectomycorrhizal fungi allow their host plants access to organic forms of N through enzymatic mineralization of the substrate and enhanced absorption of amino acids and mineral N. The cost to the plant is carbohydrates that support fungal growth and metabolism. Enrichment of soils with mineral N, as through atmospheric deposition, may affect the growth and function of these fungi by direct effects of increased N availability on fungi and indirect effects through reduced plant C allocation to roots. We tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A plant's strategy in the model is defined by its C allocation to EMF ( C f ), which in effect regulates the trade‐off between C investments in N uptake (via EMF) and C use for growth. A fungus strategy is defined by its ratio ( u ) of C allocation to reproductive growth versus N uptake components, in line with the observed trade‐off between intrinsic growth rate and potential N uptake capacity (measured as efficiency of protein mineralization) among EMF species (Eaton & Ayres, ). Changes in u may reflect both phenotypic plasticity and changes in active EMF community (species) composition.…”
Section: Descriptionmentioning
confidence: 97%
“…A plant's strategy in the model is defined by its C allocation to EMF ( C f ), which in effect regulates the trade‐off between C investments in N uptake (via EMF) and C use for growth. A fungus strategy is defined by its ratio ( u ) of C allocation to reproductive growth versus N uptake components, in line with the observed trade‐off between intrinsic growth rate and potential N uptake capacity (measured as efficiency of protein mineralization) among EMF species (Eaton & Ayres, ). Changes in u may reflect both phenotypic plasticity and changes in active EMF community (species) composition.…”
Section: Descriptionmentioning
confidence: 97%
“…Most ECM fungal taxa produce a diversity of extracellular and cell wall-bound hydrolytic and oxidative enzymes that mobilize the release of smaller organic molecules (potential C, N, or P sources) from soil organic matter (SOM) [17], including polyphenol-protein complexes. Studies have revealed substantial interspecific differences in ECM enzymatic activities [18][19][20][21][22][23][24][25][26][27][28]. Such differences can be predicted in part by ECM life history strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Ectomycorrhizal fungi may respond to shortages in host C allocation by up-regulating the activity of enzymes used to obtain labile carbohydrates [13], while changes in the relative availabilities of N and P are known to modify the activity of extracellular N-and P-mobilizing enzymes. For example, N fertilization could accelerate the degradation of easily decomposable litter and reduce the activity of extracellular ECM enzymes targeting recalcitrant litter with high levels of lignin and complex organic forms of N [24][25][26][27][28]. Both outcomes may reflect the stimulation or repression of different sets of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…N is an essential nutrient for EMF (Smith & Read, 1997) but is spatially, temporally and chemically heterogeneous in soil (Robertson et al ., 1988; Cain et al ., 1999). This may have selected EMF to evolve diverse N extraction and utilization traits and is consistent with culture experiments showing that different species of EMF have different growth responses to different forms and levels of N (Dickie et al ., 1998; Eaton & Ayers, 2002; Lilleskov et al ., 2002b). Soils at Cedar Creek are N impoverished and, as in many terrestrial ecosystems, plant growth is limited by N supply (Tilman, 1987).…”
mentioning
confidence: 99%